2019
DOI: 10.3389/fncel.2019.00393
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Control of Axonal Transport: The Extreme Case of Organismal Ageing

Abstract: A fundamental question in cell biology is how cellular components are delivered to their destination with spatial and temporal precision within the crowded cytoplasmic environment. The long processes of neurons represent a significant spatial challenge and make these cells particularly dependent on mechanisms for long-range cytoskeletal transport of proteins, RNA and organelles. Although many studies have substantiated a role for defective tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 138 publications
(161 reference statements)
0
18
0
Order By: Relevance
“…Decreased neuronal health may, therefore, be contributing to reduced mitochondrial motility, as may the process of aging. Indeed, we have previously reported that the dynamics of signaling endosome transport in vivo remain unaltered in aged wild-type mice (Sleigh and Schiavo, 2016 ; Sleigh et al, 2020a ), whereas mitochondrial transport is known to be altered in old animals (Mattedi and Vagnoni, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased neuronal health may, therefore, be contributing to reduced mitochondrial motility, as may the process of aging. Indeed, we have previously reported that the dynamics of signaling endosome transport in vivo remain unaltered in aged wild-type mice (Sleigh and Schiavo, 2016 ; Sleigh et al, 2020a ), whereas mitochondrial transport is known to be altered in old animals (Mattedi and Vagnoni, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…They comprise the ‘dying‐back’ pathology, that is, the degeneration of axons starting at their distal ends; this can be observed in hereditary diseases including CMT and hereditary motor sensory neuropathy (HMSN), HSP, giant axonal neuropathy (GAN), adrenomyeloneuropathy (AMN) and in most forms of acquired axonopathies (Boxes 1 and 2). A further common observation is the occurrence of blocked transport as a key feature of axonopathy (Brady & Morfini, 2017; De Vos, Grierson, Ackerley, & Miller, 2008; Guo, Stoklund Dittlau, & Van Den Bosch, 2020; Millecamps & Julien, 2013; Prior et al, 2017; Sleigh, Rossor, Fellows, Tosolini, & Schiavo, 2019), which is also considered a hallmark of ageing neurons (Mattedi & Vagnoni, 2019). Furthermore, there are many reports of axon swellings; as pointed out by Mike Coleman: ‘axonal spheroids, or smaller varicosities, which can be broadly termed axonal dystrophy, are almost universal in neurodegenerative diseases of the CNS, probably as manifestations of a major pathway of CNS axonal death’ (Coleman, 2005).…”
Section: Is There a Common Pathology?mentioning
confidence: 99%
“…In contrast to the detrimental effects of increased tethering, reducing MERCs by knockdown of pdzd8 in Drosophila neurons dramatically delayed age-associated decline in locomotor activity and significantly extended median lifespan compared to control animals. Since decline in mitochondrial transport is proposed to contribute to neuronal aging (Vagnoni & Bullock, 2018), we hypothesized that reducing tethering in the aging flies might be protective by allowing sustained mitochondrial motility (Mattedi & Vagnoni, 2019). However, we detected no change in the percentage of motile mitochondria in larval neurons with reduced pdzd8 expression.…”
Section: Discussionmentioning
confidence: 99%
“…While mitochondrial motility is important for neuronal health, it remains an open question whether decline of mitochondrial transport in neurons contributes to aging (reviewed in (Mattedi and Vagnoni 2019)). We first tested the hypothesis that decreased ER-mitochondrial tethering contributes to the protective effect of pdzd8 downregulation in aging through changes in mitochondrial motility.…”
Section: Modulating Mercs Causes Axonal Transport and Nmj Defectsmentioning
confidence: 99%